2018
DOI: 10.1111/bcp.13534
|View full text |Cite
|
Sign up to set email alerts
|

The effect of itraconazole and rifampicin on the pharmacokinetics of osimertinib

Abstract: Osimertinib can be co-administered with CYP3A4 inhibitors, but strong CYP3A inducers should be avoided if possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 49 publications
3
52
1
Order By: Relevance
“…Patients with cystic fibrosis have highly variable pharmacokinetics and steady‐state sputum concentrations of itraconazole often fall below the minimum inhibitory concentration (MIC 90 ) for A. fumigatus in most subjects . High plasma concentrations of itraconazole can lead to significant drug–drug interactions (DDI) and significantly impact the pharmacokinetics of other drugs through inhibition of cytochrome p450 3A4 in the liver and increasing plasma exposure has been linked to a greater probability for adverse events (AEs) . Poor pharmacokinetics and risks associated with its side effect profile limit itraconazole therapeutic efficacy …”
Section: Introductionmentioning
confidence: 99%
“…Patients with cystic fibrosis have highly variable pharmacokinetics and steady‐state sputum concentrations of itraconazole often fall below the minimum inhibitory concentration (MIC 90 ) for A. fumigatus in most subjects . High plasma concentrations of itraconazole can lead to significant drug–drug interactions (DDI) and significantly impact the pharmacokinetics of other drugs through inhibition of cytochrome p450 3A4 in the liver and increasing plasma exposure has been linked to a greater probability for adverse events (AEs) . Poor pharmacokinetics and risks associated with its side effect profile limit itraconazole therapeutic efficacy …”
Section: Introductionmentioning
confidence: 99%
“…7 Coadministration of osimertinib with itraconazole (strong CYP3A4 inhibitor) resulted in a minor increase (24% area under the plasma concentration-time curve [AUC] increase) in osimertinib exposure, which was not clinically relevant, and coadministration with rifampicin (CYP3A4 inducer) decreased the maximum plasma concentration after multiple dosing (C ss,max ) and AUC from time zero to the end of dosing interval (AUC τ ) of osimertinib by 73% and 78%, respectively. 12 Recently, it was reported that osimertinib may also cause induction of CYP1A1 enzymes in vitro, 13 although no evidence has been observed in the clinic. 14 P-glycoprotein (P-gp), a 170-kDa glycosylated transmembrane protein, is the most studied drug efflux pump that extrudes a variety of drugs from the cell.…”
mentioning
confidence: 99%
“…23 However, the absolute bioavailability of osimertinib has not been reported. 25,26 However, the strong CYP3A inducer rifampicin significantly decreased the exposure of osimertinib. 24 In PK studies, the concentration and exposure of osimertinib was not affected by coadministration with food, omeprazole, or the CYP3A and P-glycoprotein inhibitor itraconazole.…”
mentioning
confidence: 99%
“…24 In PK studies, the concentration and exposure of osimertinib was not affected by coadministration with food, omeprazole, or the CYP3A and P-glycoprotein inhibitor itraconazole. 25,26 However, the strong CYP3A inducer rifampicin significantly decreased the exposure of osimertinib. 25 For this reason, labeling recommendations for osimertinib include avoidance of strong inducers of CYP3A.…”
mentioning
confidence: 99%
See 1 more Smart Citation